Investigation of The Process of Supportive Education Designed for The Reading Skills of a Student with Hearing Loss in Inclusion Environment - Ezgi Tozak; H. Pelin Karasu; Ümit Girgin (Anı Publishing, 2018)
In this study, it was aimed to examine the supportive service designed for the reading teaching of a student with hearing loss who is in the first grade primary school. The study was designed as an action research. The participant of this study consisted of a student with hearing loss who is in first grade primary school with his normally hearing peers, researcher/teacher, parents of the student, a classroom teacher, a teacher in the rehabilitation center and validity committee members. The data were obtained through researcher diary, interviews, observations, records of validity committee meetings, the documents. Data collection process and analysis were performed simultaneously. It was noted that the activities used in the supportive education were in parallel to the Turkish Curriculum and the Guidelines. The activities were diversified and systematically repeated. Inferring from the research findings, it can be said that the hearing loss students in the inclusion environment benefited from the supportive service practices designed for the reading skill acqusition and development.